The contribution of mycosporine-like amino acids, chromophoric dissolved organic matter and particles to the UV protection of sea-ice organisms in the Baltic Sea1. Issue 5 (6th May 2015) - Piiparinen, Jonna; Enberg, Sara; Rintala, Janne-Markus; Sommaruga, Ruben; Majaneva, Markus; Autio, Riitta; Vähätalo, Anssi V.
<x xml:space="preserve">Abstract</x> Variety of mycosporine-like amino acids, chromophoric dissolved organic matter and deposited atmospheric particles provide UV-protection for sea-ice organisms.